Influence of Home Environment on Participation in Home Activities of Children with an Autism Spectrum Disorder - Divya Sood OTD, OTR/L; Patti LaVesser Ph.D., OTR; Caren Schranz DrOT, MS, OTR/L (Scholarworks @ WMU, 2014)
Background: This study explored the key physical and social factors within the home environment that influence the participation of children with an ASD in home activities. Method: Step 1 used a correlational research design to identify relationships between the home environment and participation patterns of children with ASD. Twenty-two children, ages 3 to 6 years, with a diagnosis of ASD participated. Data were collected using the Preschool Activity Card Sort (PACS), Home Observation for Measurement of the Environment Inventory (HOME), Parenting Stress Index (PSI), Social Responsiveness Scale (SRS), and Hollingshead Four Factor Index of Social Status (ISS). In Step 2, an electronic survey gathered information from 20 occupational therapists, attempting to identify their perceptions related to factors within the home environment that influence the participation of children with ASD. Results: Significant correlations were found among parenting stress, the availability of learning materials, and parent responsiveness toward the child and the participation patterns of children in home activities. Themes relating to designated play areas for children at home, parents' awareness of the needs of the child, and parents' responsiveness toward their child emerged from the occupational therapists' qualitative survey data. Conclusion: The results indicated that home environments do contribute to a child's ability to participate in home activities.